2022
DOI: 10.3389/fvets.2022.1038855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic and international travel ban on elephant tourist camp management in northern Thailand

Abstract: The COVID-19 pandemic has had a significant impact on the tourism industry, especially in Thailand. Starting in April 2020, the Thai government banned international travel and all elephant tourist camps closed. A wide variety of management changes were implemented because of the lack of income from tourists. This study surveyed 30 camps that cared for >400 elephants in northern Thailand to obtain information on camp, elephant, and mahout management during the COVID-19 pandemic from April 2020 to 2022 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…It was surprising to see no seasonality effect on fGCMs in this study because numerous previous studies of captive elephants in Thailand showed that fGCM concentrations were higher in the winter season, which also corresponds to the high tourist season [46,100]. However, this study was conducted during the international travel ban in Thailand due to COVID-19 restrictions when all camps were closed [104], so this is the first evidence that seasonal changes in fGCMs may be directly related to tourist numbers and activities rather than environmental changes.…”
Section: Discussionmentioning
confidence: 87%
“…It was surprising to see no seasonality effect on fGCMs in this study because numerous previous studies of captive elephants in Thailand showed that fGCM concentrations were higher in the winter season, which also corresponds to the high tourist season [46,100]. However, this study was conducted during the international travel ban in Thailand due to COVID-19 restrictions when all camps were closed [104], so this is the first evidence that seasonal changes in fGCMs may be directly related to tourist numbers and activities rather than environmental changes.…”
Section: Discussionmentioning
confidence: 87%
“…Before the countrywide lockdown, elephants were involved in riding with a saddle (Camp B, C, E, and F) or bareback (Camp B), elephant shows (Camp B and C), and tourist feeding (all camps). After the lockdown, all tourist activities ceased ( Supplementary Table 1 ) ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected monthly for the first year (April 2020 to April 2021), and then every 4 months for the second year (May 2021 to April 2022), resulting in 16 collections that were then divided into seven time periods (T01-T07) ( Figure 1 ). Pre COVID-19 data (T00) obtained from Supanta et al ( 12 ) were included in some comparisons.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations